Brain Magnetic Resonance Imaging Characteristics of Anti-Leucine-Rich Glioma-Inactivated 1 Encephalitis and Their Clinical Relevance: A Single-Center Study in China - Shao, Xiali; Fan, Siyuan; Luo, Huan; Wong, Ting Yat; Zhang, Weihong; Guan, Hongzhi; Qiu, Anqi (Frontiers in Neurology, 2021)
Objective: To characterize the magnetic resonance imaging (MRI) features of anti-leucine-rich glioma-inactivated 1 (LGI1) encephalitis and explore their clinical relevance. Methods: Patients with anti-LGI1 encephalitis who underwent MRI at our center were included in this study. Baseline and follow-up MRI characteristics were evaluated, and relationships between lesion location and clinical symptoms were analyzed. The extent of signal abnormalities within the lesion overlap region was measured and correlated with modified Rankin Scale scores and serum antibody titer. Results: Seventy-six patients were enrolled, of which 57 (75%) were classified as MR positive. Brain lesions were located in medial temporal lobe (MTL) (89%) and basal ganglia (BG) (28%). Hippocampus and amygdala were lesion hubs with more than 50% lesion overlap. BG lesions were found in 30% of patients with faciobrachial dystonic seizure (FBDS) and only 7% of patients without FBDS (p = 0.013). Meanwhile, MTL lesions were more commonly observed in patients with memory impairment (70% vs 0%, p = 0.017). MRI features included hyperintensity and edema at baseline, as well as hypointensity and atrophy at follow-up. Correlations between signal intensity of lesion hubs (including hippocampus and amygdala) and modified Rankin Scale scores were found on T2 (r = 0.414, p < 0.001) and diffusion weighted imaging (r = 0.456, p < 0.001). Conclusion: MTL and BG are two important structures affected by anti-LGI1 encephalitis, and they are associated with distinctive symptoms. Our study provided evidence from Chinese patients that BG lesions are more commonly observed in patients with FBDS, potentially suggesting BG localization. Furthermore, in addition to supporting diagnosis, MRI has the potential to quantify disease severity.